Assessing the Declaration and Address: Hermeneutics vs. Unity in Stone-Campbell Theology - Weedman, Mark (Stone-Campbell journal, 2011)
Thomas Campbell's vision for unity in the Declaration and Address left his followers with a choice of whether to emphasize unity or the unique "Scripture only" hermeneutic. Second-generation Campbellites reversed Campbell's emphasis on unity by instead emphasizing the priority of the hermeneutic; unity remained important but secondary to the hermeneutic. Rereading the Declaration and Address helps us recognize the importance of a "unity ecclesiology" to Campbell's argument and understand that such an ecclesiology might help us move forward with his plea for unity.